2019
DOI: 10.1038/s42004-019-0225-1
|View full text |Cite
|
Sign up to set email alerts
|

Preferentially oriented large antimony trisulfide single-crystalline cuboids grown on polycrystalline titania film for solar cells

Abstract: Photovoltaic conversion of solar energy into electricity is an alternative way to use renewable energy for sustainable energy production. The great demand of low-cost and efficient solar cells inspires research on solution-processable light-harvesting materials. Antimony trisulfide (Sb 2 S 3) is a promising light-harvester for photovoltaic purposes. Here we report on the in situ grown monolayer of preferentially oriented, large Sb 2 S 3 single-crystalline cuboids on a polycrystalline titania (TiO 2) nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 46 publications
(71 reference statements)
3
63
0
Order By: Relevance
“…Noticeably, it has been well demonstrated that the Sb 2 S 3 crystallization for efficient solar cells normally takes place at 300−330 °C. [ 2,16–21 ] This article mainly focuses on the R effect on the Sb 2 S 3 film formation and the solar cell performance, and we fix the annealing temperature at 320 °C for the Sb 2 S 3 film crystallization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Noticeably, it has been well demonstrated that the Sb 2 S 3 crystallization for efficient solar cells normally takes place at 300−330 °C. [ 2,16–21 ] This article mainly focuses on the R effect on the Sb 2 S 3 film formation and the solar cell performance, and we fix the annealing temperature at 320 °C for the Sb 2 S 3 film crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, the [221]‐orientation favors the effective charge transport toward collection electrodes. [ 21 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both classes of materials have shown very promising efficiencies to date under 1-sun illumination. [79][80][81] We note that Sb 2 S 3 is limited by the formation of self-trapped excitons, which leads to unavoidable losses at room temperature and limits the open-circuit voltage. Nevertheless, Sb 2 S 3 solar cells have achieved 6% PCE under 1-sun illumination, with an estimated 1-sun efficiency limit of 16%.…”
Section: Future Ipv Potential Of Lead-free Perovskite-inspired Materialsmentioning
confidence: 99%
“… 6 , 11 14 Ultrafast self-trapping of excitons in antimony chalcogenides, and in particular of Sb 2 S 3 , has been ascribed to the partly one-dimensional nature of the crystal and would set an intrinsic limitation for this family of materials. 6 , 15 , 16 A completely distinct effect, however, has been pointed out as the dominant limitation, namely the recombination of photogenerated carriers at interface traps. 8 , 17 , 18 In particular, the interface of Sb 2 S 3 with TiO 2 presents positively charged vacancies whith trap states below the conduction band.…”
Section: Introductionmentioning
confidence: 99%